CRITICAL DISCOURSE ANALYSIS ON DONALD TRUMP’S STRATEGY AGAINST HIS ADDRESSEE TO WIN THE US ELECTION - Sujito sujito; Indriana Indriana; Wildan Mahir Muttaqin (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2019)
Critical Discourse Analysis (CDA) deals with long term analysis of fundamental causes and consequences of issues. This paper is an attempt to explain how a single issue, that is the US presidential election, is correlated by the existence of jihadist militant and manipulated using political ideology. This study also examines the persuasive strategies of Donald Trump to win the US 2016 Election. In this study, van Dijk’s (2004) frameworks of Politics, Ideology, and Discourse is used to detect discursive structure within the transcript of Donald Trump’s speech and analyze the manner in which language can be a tool at the hands of speakers to persuade and create agreement toward the hearer. The macro strategy of positive self-representation and negative other representation, plus the other 25 more subtle strategies has become one significant way in the creation and neutralization of ideology and personal opinion. The application of this dichotomous categorization in CDA of Donald Trump’s strategy toward his addressee to win the US election has asserted the fact that ideological manipulations are used, expressed, enacted and implanted through discursive structures to persuade the audiences. The findings of this study can be conducive to expand students’ critical thinking abilities in comprehension and production of language and also in revitalizing the neglected construct of language proficiency.